Rolling the Boulder Uphill: The African Union, Constitutional Amendments, and the Struggle for Democracy and Rule of Law - Nxumalo, Sfiso Benard (As-Siyasi: Journal of Constitutional Law, 2024)
Constitutional amendments in Africa often challenge the principles of constitutionalism, democracy, good governance, and the rule of law. While constitutions are designed to be stable and reflect a nation's enduring values, amendments frequently focus on extending presidential terms, weakening the separation of powers, and undermining judicial independence. Domestic mechanisms to safeguard against such changes are often insufficient, with constitutional provisions and referenda susceptible to manipulation. This paper examines the African Union (AU) and Regional Economic Communities (RECs) in addressing these challenges. Both institutions claim a commitment to upholding constitutionalism and democracy, yet their normative frameworks inadequately address the risks of constitutional amendments. Despite the AU’s pronounced opposition to unconstitutional government changes, its response to constitutional amendments that erode governance principles has been inconsistent and undermined by uncertainties regarding subsidiarity with RECs. The paper argues that these shortcomings render the AU's efforts akin to a Sisyphean struggle, where progress toward promoting the rule of law and democracy is undone by its inaction on amendments that subvert these values. The AU and RECs must adopt a more coordinated and decisive approach to constitutional changes to prevent further erosion of African constitutionalism.